Philosophy of freedom and slavery in Paul's Epistle to the Galatians - Cisco, Charles K. (The University of Edinburgh, 2023)
Paul’s Epistle to the Galatians looms large in the history of Christian theological thought, perceived as the definitive articulation of the gospel of freedom from the slavery inherent in the observance of the Jewish law. This thesis analyzes the uses of the language of freedom and slavery in Galatians and argues that interpretational reliance upon such an anachronistic theological conception has caused the letter to be read in a manner that would have been fundamentally unintelligible to its original audience, groups of gentile messianic believers scattered throughout first century Roman Galatia. In conversation with recent scholarship that has challenged the ideas of Paul’s abandonment of Judaism or rejection of the law, it offers an alternative reading of the letter as an instance of ancient Graeco-Roman socio-political and moral philosophical discourse aimed at the formation of a pneumatic community. After an introductory survey of freedom and slavery language used literally and metaphorically in antiquity, each remaining chapter of the thesis focuses upon one of Paul’s deployments of these terms: his autobiographical retelling of an altercation in Jerusalem in which he defended believers’ freedom in Christ Jesus against enslaving false brothers, his sweeping history of humanity---both Jew and gentile---during its time in slavery under the elements of the world, and his allegorical retelling of the story of Abraham’s two sons, one slave and one free, with the concomitant command to stand in freedom and reject a yoke of slavery. The analysis places his words alongside those of his peers, the literate and culturally productive elite of the Roman world. Like many of these men, Paul deploys the language of freedom and slavery philosophically in an attempt to shape the social practices and inner lives of his readers. Unlike most of them, however, he does so as a learned expert on the Jewish scriptures and in light of his apocalyptic convictions about the resurrected and returning messiah.
The philosophy of freedom and slavery in Paul's Epistle to the Galatians
Keywords: Paul’s Epistle to the Galatians; Philosophy of freedom; slavery; Christian theological thought; Paul’s abandonment of Judaism